2016
DOI: 10.2485/jhtb.25.371
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome and Factors Affecting Dental Arch Relationship in Malay Children with Unilateral Cleft Lip and Palate (UCLP)

Abstract: The purpose of this study was to evaluate the dental arch relationship of non-syndromic Malay unilateral cleft lip and palate (UCLP) children and also assess the various congenital and postnatal treatment factors that affect dental arch relationship. Study models of 107 UCLP children were included in this study that was treated in Hospital Universiti Sains Malaysia over a period of 12 years (2000-2012). The mean age was 7.69± 2.46 (mean± SD). The dental arch relationship was assessed by GOSLON Yardstick which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…Luxor governorates while the right sided was dominant in Aswan governorate. Similar findings also reported in Tanzania population [34], Madagascar population [35] and Malaysian population [36][37][38].…”
Section: Discussionsupporting
confidence: 87%
“…Luxor governorates while the right sided was dominant in Aswan governorate. Similar findings also reported in Tanzania population [34], Madagascar population [35] and Malaysian population [36][37][38].…”
Section: Discussionsupporting
confidence: 87%
“…However, significantly lesser mandibular length (Go-Pog, p = 0.044) compared to presence of lateral incisor in the affected side of UCLP children was found. Foregoing studies also found no significant differences [5,[7][8][9][10][11][12][13][14][15]. UCLP children with positive family history of cleft had significantly lesser mandibular growth (SNB, p = 0.040) and posterior facial height (p = 0.033) and greater mandibular growth in relation to the facial plane (NA-Pog, p = 0.039).…”
Section: Discussionmentioning
confidence: 87%
“…Despite of being one of the most common orofacial birth defects, even a single study has not been conducted on any population to assess the CM outcome in relation to congenital factors that are under practice. That led us to the comparison of established outcome with the surveys of treatment outcome based on dental arch relationship [5,[7][8][9][10][11][12][13][14][15]27] and postnatal treatment factors [4] in other geographical locations. In our previous study, we assessed the postnatal treatment factors affecting CM in Japanese UCLP subjects [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations